Physiological and biochemical role of proline, trehalose, and compost on enhancing salinity tolerance of quinoa plant - Ahmed, Sium (2021)
Growth and yield measurements were decreased with salinity stress. High levels of both proline and trehalose recorded the highest values of total soluble sugars, proline, and free amino acids in both unstressed or salinity stressed plants with or without compost addition. The use of compost in soil for cultivating quinoa plants with either proline or trehalose treatments increased growth parameters, photosynthetic pigments, and yield attributes. In addition, these treatments improved the accumulation of some organic solutes in leaves and promoted antioxidant enzyme activities.